2021
DOI: 10.1007/s10943-021-01327-1
|View full text |Cite
|
Sign up to set email alerts
|

Social support through religion and psychological well-being: COVID-19 and coping strategies in Indonesia

Abstract: The Coronavirus pandemic originated in China at the end of 2019, the virus festered there for four months before spreading globally. Impacting the developed and developing world including Indonesia. It has transformed social, economic and political practices social life, everyday habits and government policies, with multi-dimensional consequences on human life. The present study endeavours to explore the relationship between religiosity, social capital, and psychological well-being of the general public, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
(73 reference statements)
3
25
1
Order By: Relevance
“…Furthermore, we did not investigate more qualitative characteristics of religious involvement in our participants, and factors like spirituality (Hill & Pargament, 2003 ), non-organizational involvement in religious practices (Anderson & Nunnelley, 2016 ) or religious coping (De Berardis et al, 2020 ; Pargament et al, 2011 ), may be linked to the effects observed in the current study. Similarly, religious coping has been shown to be significantly associated with loneliness and mental well-being during the COVID-19 crisis (Saud et al, 2021 ; Yıldırım et al, 2021 ), and was not assessed in the current study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, we did not investigate more qualitative characteristics of religious involvement in our participants, and factors like spirituality (Hill & Pargament, 2003 ), non-organizational involvement in religious practices (Anderson & Nunnelley, 2016 ) or religious coping (De Berardis et al, 2020 ; Pargament et al, 2011 ), may be linked to the effects observed in the current study. Similarly, religious coping has been shown to be significantly associated with loneliness and mental well-being during the COVID-19 crisis (Saud et al, 2021 ; Yıldırım et al, 2021 ), and was not assessed in the current study.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, we did not investigate more qualitative characteristics of religious involvement in our participants, and factors like spirituality (Hill & Pargament, 2003), non-organizational involvement in religious practices (Anderson & Nunnelley, 2016) or religious coping (De Berardis et al, 2020;Pargament et al, 2011), may be linked to the effects observed in the current study. Similarly, religious coping has been shown to be significantly associated with loneliness and mental well-being during the COVID-19 crisis (Saud et al, 2021;Yıldırım et al, 2021), and was not assessed in the current study. Furthermore, even though other studies have shown the stability of social networks in the initial months of the COVID-19 pandemic (Bond, 2021), it cannot be excluded that with such a long follow-up period that the participants may have undergone multiple changes in their social network structure, associated both with general factors (e.g., changes in the relationship status over time) and COVID-19 specific issues (e.g., losing a friend or relative due to COVID-19).…”
Section: Study Limitationsmentioning
confidence: 73%
“…This would underline that intensifying one´s spirituality during the pandemic is a strategy to cope with fears and worries, while it is nevertheless not necessarily contributing to psychological wellbeing. This might be different in other religious groups as shown for Muslims (Saud et al, 2021 ; Mahmood et al, 2021 ; Anchour et al, 2021 ).…”
Section: Discussionmentioning
confidence: 83%
“…It is well known that a person´s faith or spirituality can be a buffer against adverse life events (Weber & Pargament, 2014 ), and thus it was assumed that this resource is relevant also to cope with the adverse effects of the corona pandemic (Kowalczyk et al, 2020 ; Pirutinsky et al, 2020 ; Asadzandi et al, 2020 ; Barmania & Reiss, 2020 ; Peteet, 2020 ; Koenig, 2020 ; Edara et al, 2021 ). Also for Muslims, it was stated that religion and religious coping may buffer health anxiety during the pandemic and may help to stabilize their wellbeing (Saud et al, 2021 ; Mahmood et al, 2021 ; Anchour et al, 2021 ). While these findings might be true for the first phases of the pandemic, it may not be true for all societies and specifically for the later phases of the pandemic (Büssing et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firm commitment and job satisfaction are positively associated with psychological capital, according to current research on the impact of psychological capital on individual performance, attitudes, and behaviors at work ( Kang and Busser, 2018 ). Furthermore, according to Saud et al (2021) , psychological capital has a significant association with employee innovative and optimistic behaviors while dipping down negative attitudes of employees like anxiety. It can be considered that psychological capital can minimize employee anxiety and stress, and maximize employee productivity.…”
Section: Literature Reviewmentioning
confidence: 99%